Functional Neuroanatomy of the Human Accommodation Response to an “E” Target Varying from -3 to -6 Diopters - Lv, Xiaoli; Chen, Yilei; Tan, Wenli; Yu, Ying; Zou, Hong; Shao, Yu; Zan, Songhua; Tao, Jinhua; Miao, Wanhong (Frontiers in Integrative Neuroscience, 2020)
Background: We aimed to identify the functional brainnet works involved in the regulation of visual accommodation by contrasting the cortical functional areas evoked by foveal ﬁxation to an “E” target,which were subservient to the accommodation responses to a -3/-6diopter stimulus. Methods: Neural activity was assessed in healthy volunteers by changes in blood oxygen level-dependent (BOLD)signals measured with functional magnetic resonance imaging (fMRI).Twenty-five right-handed subjects viewed the “E” target presented in a hierarchical block design.They parti-cipated in two monocular tasks: (i)sustained foveal ﬁxation upon a “E” target on white background at 33 cm(-3.03D accommodative demand)and (ii)sustained fixation through an attached -3D concave lens (-6D accom-modative demand) in front of the fixated eye; each condition cycled through a standard alternating 30-sec eye open/30-sec eye closed design to provide the BOLD contrast.The total sustained period was 480 sec. Results: The contrast between the -3D and the rest condition revealed activation in the occipital lobe (lingual gyrus, cuneus, calcarine_L, and calcarine_R); cerebellum (cerebellum_crus1_L and cerebellum_6_L); precentral lobe(precentral_R); frontal lobe(frontal_inf_oper_R and fron-tal_mid_R);and cingulate cortex(cingulum_ant_L). With the -3D concave lenses (-6D accommodative demand) in front of the fixated eye, the voxel size and magnitudes of activation in the occipital lobe and cerebellum were greater than with the -3D accommodative demand; emergent activated brain areas included the parietal lobe(bilateral precuneus lobe and right supramarginal gyrus); the precentral lobe and cingulate cortex failed to reach the threshold in the -6D vs. rest contrast. In the -3D and -6D contrast comparison,the frontal lobe (frontal_sup_medial_L) and parietal lobe (precuneus_L andprecuneus_R) passed the significance threshold of cluster-level family wise error (FWE)correction. The mean activation in the -3D and -6D contrast revealed an incremental summation of the activations than that found in the previous -3D vs. rest and -6D vs. rest comparisons. Conclusions: Neural circuits were selectively activated during the -3D/-6D ac-commodative response to blur cues. During visual accommodation, top-down systems, not only cognitive-perceptual processing but also mental processing,were engaged within the accommodative system.